(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of this research is to show the relationship between bank financing and gross domestic product in the Iraqi business environment for the period (2010-2020), and to achieve the purposes of the research, the analytical method was relied on, which is based on the inductive and deductive approaches through descriptive analysis and mathematical analysis of the historical development of data and extrapolation of the financial and banking reality In Iraq, and then devise the effects and the consequences of them in order to reach the achievement of the research objectives. Through the standard analysis of the study, the results showed that there is a direct positive relationship between monetary financing and GDP in Iraq for the short and long term, while there is a direct positive relationship between pledge financing and GDP for the short term, and the relationship was inverse in the long term. The study recommended the need to support small projects by financing them because of their active role in the process of economic and social development through their contribution to the gross domestic product and the creation of job opportunities, in addition to their export activity. Therefore, bank financing mechanisms are required for these projects due to their important role in the Iraqi business environment.